Pengaruh Layanan Pendidik Terhadap Kepuasan Orang Tua siswa di TK Amal Ikhlas II Tapung - Linda Linda (Jurnal Pendidikan Tuntas, 2024)
One of the efforts to improve the quality of a nation is to improve the quality of education. The quality of education services from the institution greatly affects customer satisfaction, PAUD services at Amal Ikhlas II Tapung Kindergarten have not run optimally. Many factors influence, namely internal factors, namely from the institution itself and external factors, namely factors from outside the school (parents and society). This research is a quantitative approach with a descriptive method that describes the effect of educational services of PAUD institutions on the satisfaction of parents of students at Amal Ikhlas II Tapung Kindergarten. In the aspect of parent satisfaction with educators, the accumulated highest score and lowest score were 3.48 and 3.32. To maximize the way the school involves parents in school programs, the school should be more open and intense meetings or meetings need to be held so that parents feel directly involved in program activities carried out by the school. Keywords: Service, Educator, Satisfaction